La burguesía mercantil leonesa en el siglo XVIII (Estudios humanísticos. Geografía, historia y arte, 1991)
In the post Middle Ages two types of mercantile or commercial bourgeoise emerged in the province of León. On the one hand know as urban merchants, with permanent shops, whose activities drew them closer and closer to the rural environment and agricultural products, and one the other the muleteers from de the region of Astorga, who not only matained large agricultural developments but also evolved an important mercantile activity and monopolised part of the traffic betwee n Galicia and Castile.Although the social attitudes of both bourgeoisies were conditioned during the post Middle Ages by their links with the different areas in wich they moved, both groups were higly conditioned by the dominant system, in which a society with strictly defined social classes and, as a result of this, certain feudal relations, was still maintained.